Patients with chronic mild or moderate traumatic brain injury have abnormal longitudinal brain volume enlargement more than atrophy. (May 2021) - Ross, David E; Seabaugh, John D; Seabaugh, Jan M; Plumley, Jennifer; Ha, Junghoon; Burton, Jason A; Vandervaart, Andrew; Mischel, Ryan; Blount, Alyson; Seabaugh, Daniel; Shepherd, Katherine; Barcelona, Justis; et al.
Introduction: Many studies have found brain atrophy in patients with traumatic brain injury (TBI), but most of those studies examined patients with moderate or severe TBI. A few recent studies in patients with chronic mild or moderate TBI found abnormally large brain volume. Some of these studies used NeuroQuant®, FDA-cleared software for measuring MRI brain volume. It is not known if the abnormal enlargement occurs before or after injury. The purpose of the current study was to test the hypothesis that it occurs after injury. Methods: 55 patients with chronic mild or moderate TBI were compared to NeuroQuant® normal controls ( n  > 4000) with respect to MRI brain volume change from before injury (time 0 [t0], estimated volume) to after injury (t1, measured volume). A subset of 36 patients were compared to the normal controls with respect to longitudinal change of brain volume after injury from t1 to t2. Results: The patients had abnormally fast increase of brain volume for multiple brain regions, including whole brain, cerebral cortical gray matter, and subcortical regions. Discussion: This is the first report of extensive abnormal longitudinal brain volume enlargement in patients with TBI. In particular, the findings suggested that the previously reported findings of cross-sectional brain volume abnormal enlargement were due to longitudinal enlargement after, not before, injury. Abnormal longitudinal enlargement of the posterior cingulate cortex correlated with neuropathic headaches, partially replicating a previously reported finding that was associated with neuroinflammation.